Assistência ao parto e nascimento e suas repercussões na relação inicial mãe-bebê - Sousa, Danielle Ferreira de (Universidade Federal de São Carlos, 2022)
Introduction: Childbirth is a unique and transforming event marked by hormonal and physiological changes and significant social representations. The childbirth experience has unfoldings that can directly affect the woman's health and her bond with the baby. Understanding the importance of the relationship between mother and child, its repercussions on child development and the need for constant monitoring of childbirth care practices, this study on obstetric violence is proposed. Objective: To investigate the existence of obstetric violence in labour and birth assistance and its impacts on the initial mother-baby interaction. Specific objectives: to verify whether the women know what obstetric violence is; to identify whether, during delivery, the women were submitted to inadequate procedures considered as obstetric violence; and to identify the possible impacts on the initial mother-baby interaction. Methodology: This is a quantitative, cross-sectional and correlational study. The study was conducted remotely, with forms made available via Google Forms and online interviews. For data collection, a characterization sheet and a Questionnaire on Childbirth Care, Birth and Obstetric Violence prepared by the research and the Questionnaire for Evaluation of the Postpartum Bond between Mother and Baby/PBQ - Portuguese translated version were used. Data were analyzed using simple and descriptive statistics, and later, for the correlational analysis of variables, statistical tests were used. Results: Sixty-two women, aged 18 to 38 years, primiparous and multiparous, who gave birth in public and private Brazilian maternity hospitals participated in this study. Regarding prenatal health education, 40.3% of the participants reported not having received any educational approaches among the highlighted themes. As for the delivery route, 53.2% of women had an expected delivery, and 46.8% had a cesarean section. Of the participants, 85.5% said they knew obstetric violence. As for the perception of the care received, 74.2% of the participants consider having received support and support from the team, and 48.4% consider not having experienced obstetric violence at the birth of their baby. In the treatment received by the team, 32.2% of the women experienced some verbal or psychological violence. Of the procedures performed during labour and delivery assistance, 48.3% were submitted to some obstetric procedure without their consent or explaining their need. Among the participants, 45.1% had skin-to-skin contact immediately after the baby's birth and breastfeeding in the first hour of life. At a 5% significance level, the bond between mother and baby measured by the PBQ index is different between mothers who reported having suffered obstetric violence and those who reported not having suffered, and mothers who reported not having suffered have lower values for this index, therefore, better bonding. Discussion: The results of the study show advances in childbirth care as highlighted in the literature, represented mainly by the low rates of episiotomy and Kristeller maneuver, access to non-pharmacological methods for pain relief, and primarily positive perceptions of parturients regarding the assistance received. However, weaknesses were found in health education actions during prenatal care, obstetric interventions performed without the consent or due clarification of the parturient women, and situations of psychological and verbal violence by health professionals. These findings are in dialogue with the literature regarding the challenges of incorporating humanized and respectful obstetric practices. The experience of obstetric violence brings to the woman physical and psychosocial implications, increased risks of maternal morbidity and mortality, and repercussions in the bonding with her baby. Health professionals must provide a positive experience to the woman and the dyad during labour and birth assistance. Conclusion: It is concluded that even in the face of advances, a scenario of assistance predominantly centred on the professional and not on the woman persists. The study highlights the importance of adopting respectful and evidence-based care practices, which put into question the impacts of inadequate care on maternal and child health, perinatal outcomes, morbidity and mortality, and, as evidenced, the establishment of the bond between mother and baby, a fundamental process for the child's healthy development.
Assistance to childbirth and its repercussions on the initial mother-baby relationship
Keywords: Violência obstétrica; Relação mãe-filho; Saúde materno-infantil; Humanização da assistência; Obstetric violence; Mother-child relations; Maternal and child health; Humanization of assistance; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL